The Role of NT-proBNP in the Diagnosis of Peripartum Cardiomyopathy with Multiple Left Ventricular Thrombus: A Case Report - Yashinta Octavian Gita Setyanda; Yaswir, Rismawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Peripartum cardiomyopathy (PPCM) is a rare but serious condition characterized by left ventricular dysfunction in late pregnancy or early postpartum. Early diagnosis is essential to prevent complications such as thromboembolism. N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a promising biomarker for the diagnosis of PPCM. Case presentation: An 18-year-old female presented with progressive shortness of breath and generalized edema. Physical examination and echocardiography revealed acute heart failure with multiple left ventricular thrombus. Very high levels of NT-proBNP (1,796 pg/mL) supported the diagnosis of PPCM. The patient was successfully treated with standard heart failure therapy and anticoagulants. Conclusion: This case report highlights the importance of NT-proBNP in the early diagnosis of PPCM and detecting of thromboembolic complications. Significant increases in NT-proBNP levels, even without obvious symptoms, should be promptly evaluated for PPCM, especially in high-risk populations.